2011
DOI: 10.1371/journal.pone.0020712
|View full text |Cite
|
Sign up to set email alerts
|

Critical Transition in Tissue Homeostasis Accompanies Murine Lung Senescence

Abstract: BackgroundRespiratory dysfunction is a major contributor to morbidity and mortality in aged populations. The susceptibility to pulmonary insults is attributed to “low pulmonary reserve”, ostensibly reflecting a combination of age-related musculoskeletal, immunologic and intrinsic pulmonary dysfunction.Methods/Principal FindingsUsing a murine model of the aging lung, senescent DBA/2 mice, we correlated a longitudinal survey of airspace size and injury measures with a transcriptome from the aging lung at 2, 4, 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 29 publications
(40 reference statements)
4
43
0
1
Order By: Relevance
“…To test whether an induction apoptosis and TGF-b1 expression by Elovl6 deficiency is mediated by ROS generation, we performed immunohistochemical staining for nitrotyrosine, a marker of oxidative stress 22 . Nitrotyrosine immunoreactivity was observed in alveolar epithelial cells in Elovl6 À / À mice but barely detected in WT mice before BLM instillation (Fig.…”
Section: Blm Treatment Decreases Elovl6 Expression In the Lungmentioning
confidence: 99%
“…To test whether an induction apoptosis and TGF-b1 expression by Elovl6 deficiency is mediated by ROS generation, we performed immunohistochemical staining for nitrotyrosine, a marker of oxidative stress 22 . Nitrotyrosine immunoreactivity was observed in alveolar epithelial cells in Elovl6 À / À mice but barely detected in WT mice before BLM instillation (Fig.…”
Section: Blm Treatment Decreases Elovl6 Expression In the Lungmentioning
confidence: 99%
“…Using a murine model of aging lung, Calvi et al demonstrated a nonlinear pattern of airspace caliber enlargement with a critical transition occurring between 8 and 12 months of age [7]. Paxson et al found that the regenerative capacity of the murine lung after pneumonectomy is progressively lost with age, with the earliest decline in the rate of lung regeneration measurable by 9 months of age [20].…”
Section: Discussionmentioning
confidence: 99%
“…Aging is associated with structural changes in the lung that leads to decreased lung function. The best known change that occurs in the lung as it ages is the alveolar enlargement, which causes a reduction in maximum achievable flow in the airways during the breathing cycle [6][7][8]. Significant widening of alveolar air space along with a size increase of interalveolar pores might facilitate the occurrence of edema.…”
Section: Introductionmentioning
confidence: 99%
“…enlargement in the absence of wall destruction [34] and is thus clearly different from pathophysiologically altered lungs of COPD patients. Indeed, lungs of aged rodents show similar "senile" changes when compared with lungs of young animals [35]. However, premature ageing in mouse models does not always recapitulate senile emphysema: senescence-accelerated mice (SAM), Klotho-, and senescence-marker protein-30 deficient mice show air space enlargement without airway wall destruction [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%